Plugging in or going wireless: strategies for interspecies electron transfer - Shrestha, Pravin Malla; Rotaru, Amelia-Elena (Frontiers in Microbiology, 2014)
Interspecies exchange of electrons enables a diversity of microbial communities to gain energy from reactions that no one microbe can catalyze. The first recognized strategies for interspecies electron transfer were those that relied on chemical intermediates that are recycled through oxidized and reduced forms. Well-studied examples are interspecies H2 transfer and the cycling of sulfur intermediates in anaerobic photosynthetic communities. Direct interspecies electron transfer (DIET) in which two species establish electrical contacts is an alternative. Electrical contacts documented to date include electrically conductive pili, as well as conductive iron minerals and conductive carbon moieties such as activated carbon and biochar. It seems likely that there are additional alternative strategies for interspecies electrical connections that have yet to be discovered. Interspecies electron transfer is central to the functioning of methane-producing microbial communities. The importance of interspecies H2 transfer in many methanogenic communities is clear, but under some circumstances DIET predominates. It is expected that further mechanistic studies and broadening investigations to a wider range of environments will help elucidate the factors that favor specific forms of interspecies electron exchange under different environmental conditions.